PENGARUH KOMUNIKASI GURU TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 SABAK AUH KABUPATEN SIAK - Agustina, Firna; Indrawati, Henny; Suarman, Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims is determinate to find out The Influence of Teacher Communication Toward Student Critical Thinking Ability. The study was conducted at SMAN 1 Sabak Auh. With a population of 45 students and all populations sampled. The research data was collected by using a questionnaire and the subsequent documentation was analyzed using simple linear regression. The result showed that teacher communication in carrying out learning included good and verry good categories, while students’ criticcal thingking ability were in the moderate category. From the result of simple linear regression analysis it can be seen that there is an influence of teacher communication on students’ critical thingking ability with a contribution of 38,6 %. This means that the better the teacher’s communication in learning will also increase the level of students’ critical thingking ability. Therefore it is expected that the teacher will continue to improve multi-way communication in the learning procces so that it can also improve students’ critical thingking ability.Key Words: Teacher Communication, Student Critical Thinking Ability